Amblyopia and strabismus: trends in prevalence and risk factors among young adults in Israel. Issue 5 (16th August 2017) - Shapira, Yinon; Machluf, Yossy; Mimouni, Michael; Chaiter, Yoram; Mezer, Eedy
Abstract : Aims: To estimate the prevalence of amblyopia, present strabismus and amblyopia risk factors (ARFs) among young adults in Israel and to analyse trends over time of prevalence rates. Methods: We conducted a cross-sectional study including 107 608 pre-enlistees aged 17.4±0.6 years born between 1971 and 1994. Across the birth years, the following trends of prevalence rates among young adults were analysed: prevalence of amblyopia, prevalence of strabismus, severity of amblyopia and prevalence of ARFs (strabismsus, anisometropia and isoametropia). Unilateral amblyopia was defined as best corrected visual acuity (BCVA) of <0.67 (6/9) in either eye or as an interocular difference of two lines or more. Bilateral amblyopia was defined as BCVA of <0.67 (6/9) in both eyes. The severity of amblyopia was classified as mild (BCVA ≥0.5 [6/12]), moderate (BCVA <0.5 [6/12] and ≥0.25 [6/24]) or severe (BCVA <0.25 [6/24]). Results: The prevalence of young adulthood amblyopia declined by 33%, from 1.2% to 0.8% (R 2 =0.87, p<0.001) across 24 birth years. This decline may be due to a drop in unilateral amblyopia from 1% to 0.6% (R 2 =0.93, p<0.001), while the prevalence of bilateral amblyopia remained stable (0.2%, p=0.12). The decline in amblyopia was apparent in mild and moderate amblyopia, but not in severe amblyopia. Strabismus and anisometropia were detected in 6–12% and 11–20% of subjects with unilateral amblyopia, respectively, without significant trends. Strabismic amblyopia remained constant in the entire population across years. Isoametropia was detected in 46–59% of subjects with bilateral amblyopia without a significant trend across birth years. Prevalence of strabismus in the study population decreased by 50%, from 1.2% to 0.6% (R 2 =0.75, p<0.001). In subjects with present strabismus, the prevalence of mild unilateral amblyopia increased, while moderate or severe unilateral amblyopia remained relatively stable. Conclusion: Among young adults, the prevalence of unilateral amblyopia, as well as the prevalence of present strabismus, decreased significantly over a period of a generation. The prevalence of strabismic, bilateral or severe (both unilateral and bilateral) amblyopia remained stable. The establishment of the national screening programme for children and the improved utility of treatment for amblyopia and strabismus coincide with these trends. Thus, it is possible that these early interventions resulted in modification of the 'natural history' of these conditions and their prevalence in adolescence.